Spatial distribution patterns of benthic macroinvertebrate functional feeding groups in two rivers of the olifants river system, South Africa - Addo-Bediako, Abraham (Informa UK Limited, trading as Taylor & Francis Group, 2021)
Benthic macroinvertebrates play a vital role in ecosystem functioning, such as nutrient cycling, primary production, decomposition and material translocation. A study was done to determine the functional feeding groups (FFGs) distribution along two streams of the Olifants River System, South Africa. There were longitudinal differences of the functional groups but were more pronounced in the Dwars River than in the Spekboom River. Collector-gatherers and collector-filterers were the most abundant groups recorded in both rivers. The least abundant groups were the shredders and scrapers in both rivers. The highest abundance of shredders in both rivers was at upstream sites (DS1 and SS1), more scrapers were found at midstream sites (DS3 and SS2), collector- gatherers and collector-filterers increased in the downstream (SS4) of the Spekboom River and predators were nearly constant in relative abundance at all sites. The relative abundance and richness of the FFGs did not conform completely to the river continuum concept (RCC). This could be related to the degradation of the catchment resulting from human activities which affected the quality of the water.
Journal article published in the Journal of Freshwater Ecology, 36:1, 97-109
Keywords: Functional feeding group; Macroinvertebrates; Land use; Water quality; Land use -- South Africa; Water quality -- South Africa; Benthic ecology